Mais que parente : relações de parentesco e gênero na comunidade quilombola ribeirão Itambé em Chapada dos Guimarães – MT - Oliveira, Adriana Martins de (2018)
This work is the realization of an ethnographic study about the experience of the Quilombola families of Ribeirão Itambé - Chapada dos Guimarães - MT along ruptures, continuities and discontinuities that marked the collectivity and the social networks that they built. The relations of kinship between the quilombolas of the remaining community show, in the anthropological field, which native categories express kinship in and out of the quilombo, that is to say, as the networks of relations with the relatives that compose the network that constitutes the community quilombola In order to think this category of relatives understood as it is in the quilombo, there are several dialogues in which they oppose the idea of blood relatives and relatives of consideration, returning to the classic division between consanguinity and affinity in the studies of kinship. That is, in Itambé, consanguinity emerges as an important, but not decisive, factor in relation to kinship, especially with regard to the meaning given to these relations. There are separations between the way men and women act in community policy. One way of doing politics that is connected to the Community Remnant Community of Quilombola do Ribeirão do Itambé in a centralizing discourse that promises to solve the situation hovers at meetings and assemblies. However, the policy is not made only during the assembly of the association. In the practices of their relations, these quilombola women operate changes and act politically. These relationships they make in kitchens, in the pasture, in the countryside, or in the city. They learn about events, their demands, and expose their opinions. In analyzing more closely, it is noted that, although these women do not actively participate in the association's processes, they are, through relationships, articulating and moving the community, they also actively participate in this struggle.